Design and Characterization of pH Dependent Phase Transition System of Almotriptan Malate for Nasal Drug Delivery System by Employing Factorial Design - Malviya, Vedanshu; Pande, Srikant (Indian Journal of Pharmaceutical Education and Research, 2024)
Introduction: Nasal medication delivery uses nasal mucosa for faster and higher drug absorption. Transmucosal nasal administration is promising. Many medicines obtain superior systemic absorption via nasal route than orally. Objectives: This research aimed to construct and characterize a pH-dependent almotriptan malate nasal in situ gel for acute migraine treatment. It eases discomfort, headaches, and migraine symptoms. Materials and Methods: Gels were delivered by changing the grouping of pH-sensitive and mucoadhesive polymers, explicitly HPMC-E15 and chitosan hydrochloride, in a cycle that was done by applying cool method Results. The range of drug content was between 95.87±0.45 to 99.58±0.56%. The pH value was measured to fall between 6.10±0.92 and 6.41±0.11. The obtained results notably agreed with the change in phase+transition, and the formulations portraits the rheology in a pseudoplastic behavior. This was a very exciting discovery. The mucoadhesiveness of all of the formulations rose with the HPMC-E15: Chitosan HCl concentration which was found to be in the range of 2133±1.58 to 3111.47±1.32 dynes/cm2 for the most effective formulations. The in vitro release of drug results of the optimized formulation, which consisted of 5 g HPMC-E15, 1 g Chitosan hydrochloride, and 1.5 g PEG400, indicated that 94.24±0.96% release occurred at the end of 12 hr. Studies using histopathology indicated that the AMF4 formulation had a non-toxic effect on the microscopic structure of the nasal mucosa when it was subjected to ex vivo permeation tests which showed the drug release of 78.85±0.87 %. Based on the findings of the stability research, a temperature range of 5ºC±3ºC is recommended for storing the formulations. Conclusion: As per these discoveries, nasal in situ gel containing almotriptan malate is probably going to turn into a selection of arrangements for treating migraines and other symptoms associated with migraines in the near future and in a nutshell, an in situ gel formulation of almotriptan malate that is pH dependent has the potential to function as an efficient method of treating migraines
Keywords: In situ Gel; Migraine; Triptan; pH Sensitive; Nasal Gel; Almotriptan Malate